"Just like us": Increasing awareness, prompting action and combating ageism through a critical intergenerational service learning project. Issue 2 (1st February 2019) - Gardner, Paula; Alegre, Rio
ABSTRACT: In the Through their Eyes Project health sciences students are partnered with older adults to explore and assess the age-friendliness of their neighborhood. Using an innovative data collection tool – 'moving interviews' – these intergenerational research teams learn about the community and each other by traveling, observing, and discussing these landscapes together. The research project culminates in a community forum where findings are presented to government officials, the housing association and aging organizations. In addition to completing the research project, students are required to keep a journal to reflect on their experience. The purpose of this study was to explore students experience participating in a critical intergenerational service learning project. Two research questions guided this inquiry: What was the experience for students and, what elements of the project are important to that experience? Student journals collected over 5 years from 191 students comprised the data for this study. Data were analyzed using a 6-phase thematic analysis process. Two key findings related to student experience emerged from the study: increased awareness and prompted to action . Elements of the course found significant to this experience included an aging simulation activity and the specific design of the project. The paper concludes with suggestions for developing and integrating critical service-learning pedagogy into gerontological education.